Prevalence, patterns, and predictors of yoga use: results of a U.S. nationally representative survey - Cramer, H; Ward, L; Steel, A; Lauche, R; Dobos, G; Zhang, Y (Elsevier, 2015)
Introduction: The purpose of this study was to investigate the prevalence, patterns, and predictors of yoga use in the U.S. general population. Methods: Using cross-sectional data from the 2012 National Health Interview Survey Family Core, Sample Adult Core, and Adult Complementary and Alternative Medicine questionnaires (N=34,525), weighted frequencies for lifetime and 12-month prevalence of yoga use and patterns of yoga practice were analyzed. Using logistic regression analyses, sociodemographic predictors of lifetime yoga use were analyzed. Analyses were conducted in 2015. Results: Lifetime and 12-month prevalence of yoga use were 13.2% and 8.9%, respectively. Compared with nonpractitioners, lifetime yoga practitioners were more likely female, younger, non-Hispanic white, college educated, higher earners, living in the West, and of better health status. Among those who had practiced in the past 12 months, 51.2% attended yoga classes, 89.9% used breathing exercises, and 54.9% used meditation. Yoga was practiced for general wellness or disease prevention (78.4%), to improve energy (66.1%), or to improve immune function (49.7%). Back pain (19.7%), stress (6.4%), and arthritis (6.4%) were the main specific health problems for which people practiced yoga. Conclusions: About 31 million U.S. adults have ever used yoga, and about 21 million practiced yoga in the past 12 months. Disease prevention and back pain relief were the most important health reasons for yoga practice. Yoga practice is associated with age, gender, ethnicity, SES, and health status.